KOMPETENSI GURU BAHASA ARAB DALAM PEMANFAATAN TEKNOLOGI PEMBELAJARAN DALAM PEMBELAJARAN BAHASA ARAB : Studi Kasus MAN 1 MOJOKERTO - Nurul Maulidya; Muhammad Hafidz (Institut Kariman Wirayudha Sumenep, 2024)
One of the things that must be owned as a support for teachers so that they can provide learning properly and correctly is competence. Teacher performance will be helped in carrying out their duties as a teacher by having competence. Pedagogic competence and professional competence are competencies that have indicators of the use of learning technology which are aspects that are needed by teachers and students in today's era. The Arabic language teacher is no exception. Arabic teachers really need to understand learning competencies in the use of technology. Learning Arabic can be more easily understood by students with technology. Because of this, researchers are interested in conducting research related to Arabic learning competencies in the use of learning technology for Arabic language teachers at MAN 1 Mojokerto. In this study, the researcher formulated three problem formulations. This research uses qualitative research methods with the type of case study research. This study uses data collection techniques of observation, interviews and documentation. This study aims to see the ability of Arabic teachers at MAN 1 Mojokerto in use of learning technology From the results of this study, it can be concluded that: (1) The competence of Arabic teachers in the use of technology in finding material gets a competency assessment 3 or is categorized as good. (2) The competence of Arabic language teachers in the use of technology in developing learning media gets a competency assessment of 4 or is categorized as very good. (3) The competence of Arabic language teachers in the use of technology in the learning process gets a competency assessment of 4 or is categorized as very good. For the total competency assessment, getting a score of 3.6 or can be categorized as good. Keyword : Learning Competence, Use of technolog